Factors Affecting Vietnamese Students’ Intention To Start Their Own Busines - Do, Thi Cam Thuy (H. : ĐHQGHN, 2020)
The study aims to determine the factors that influence the intention to start businesses of business students at the universities/ colleges in Vietnam. In this study, I examined the factors that might influence entrepreneurial intention among students in Vietnam. My research model was built based on the application of two theories: The Entrepreneurial Event Model (Shapero and Shokol, 1982) and Ajzen’s Theory of Planned Behavior (1991). More specifically, my research seeks to examine the role of entrepreneurial desire, entrepreneurial confidence, university’s support, gender, parents’ self-employment history and family’s support in promoting Vietnam students’ entrepreneurial attitudes.